Thesis Supervisors and Students’ Perceptions of Online Thesis Consultation at English Language and Literature Department of Universitas Negeri Padang - Kurnia Ulfatun Hasanah; Sitti Fatimah (Journal of English Language Teaching, 2023)
The aims of the study to know how supervisors’ and students’ perception of online thesis consultation for supervisors and students in English Language and Literature Department at UNP. This study used descriptive quantitative research to investigate the perceptions of students and supervisors regarding online thesis consultation. This research used questionnaire and interview to collect the data. The sample of this research was 30 students of final semester period 2017 and 2018 and 7 supervisors who filled out questionnaires. The questionnaire in this study is a closed questionnaire that is used to gather information.It was designed based on the aspect of successful online consultation and aspect of effective communication . The interview guidelines was designed based on the aspect of successful online consultation. The results of the perception of 7 supervisors showed 81.75 % and 30 students showed that 76.6 % was in good category or positive. But from the supervisor it is still classified as negative based on the interview. Based on the results of the interview, the students had negative and positive perceptions about online thesis consultation. The positive, online consultation had more efficient and flexible time, cost effective, and the results of discussed with supervisor can be recorded. While negative perceptions is delayed feedback or responses, misunderstanding, lack of unlimited Zoom Meetings.